A bidirectional causal relationship study between mental disorders and male and female infertility - Chen, Xiangyu; Hao, Xuexue; Xie, Lijun; Liu, Xiaoqiang (Frontiers in Psychiatry, 2024)
The relation between mental disorders (MDs) and infertility can be reciprocal. But exactly which MD affects infertility remains controversial. Our aim was to use Mendelian randomization (MR) to explore bidirectional causality between 15 MDs and male infertility and female infertility.The data of MDs, male infertility, and female infertility were derived from published genome-wide association studies (GWAS). The inverse variance weighted method was considered to be the main analytical approach. Sensitivity analysis was performed using MR-Egger, Cochran's Q, radial MR, and MR-PRESSO tests.Results: Our results found that mood disorders (OR, 1.4497; 95% CI, 1.0093 -2.0823; P = 0.0444) and attention deficit hyperactivity disorder (OR, 1.3921; 95% CI, 1.0943 -1.7709; P = 0.0071) were positively correlated with male infertility, but obsessivecompulsive disorder (OR, 0.8208; 95% CI, 0.7146 -0.9429; P = 0.0052) was negatively associated with male infertility. For females, anorexia nervosa (OR, 1.0898; 95% CI, 1.0070 -1.1794; P = 0.0329), attention deficit hyperactivity disorder (OR, 1.1013; 95% CI, 1.0041 -1.2079; P = 0.0406), and major depressive disorder (OR, 1.1423; 95% CI, 1.0213 -1.2778; P = 0.0199) increased risk of infertility. In reverse relationship, female infertility increased the incidence of bipolar disorder (OR, 1.0009; 95% CI, 1.0001 -1.0017; P = 0.0281).We demonstrated the association between five MDs and male or female infertility. Female infertility was also found to be associated with an increased risk of one MD. We look forward to better designed epidemiological studies to support our results.